THE SHELL ULTRASTRUCTURE OF THE GENUS GLYCYMERIS DA COSTA, 1778: A COMPARISON BETWEEN FOSSIL AND RECENT SPECIMENS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
New data about the shell ultrastructure of species of the genus Glycymeris are obtained through a comparison between the fabric of recent specimens from Brittany (France) and fossil specimens collected from the Lower Pleistocene Castell’Arquato Formation cropping out along the Arda River in Western Emilia (Italy). This comparison, made using Scanning Electron Microscope (SEM), results in a strong similarity between the two fabrics, highlighting the good preservation of fossil ones. Both fossil and recent specimens show a well preserved outer simple crossed lamellar layer and an inner irregular and cone complex crossed lamellar layer. The inner and outer layers are separated by an irregular simple prismatic pallial myostracum. These mineralized layers are penetrated by parallel, not ramified and not bifurcated cylindrical tubules, which represent a peculiar character of the Arcoida shells. This analysis provides a more complete picture of Glycymeris shell ultrastructure. It shows that Glycymeris shell fabric has not changed for the last 2 million years and that the fossil specimens are pristine. Furthermore new data on the pattern and origin of tubules are reported, allowing to conclude that it is unlikely that they have a deterrence function for boring organisms. They may instead function to increase the volume of the organic content of the shell at lower metabolic cost without increasing the shell surface.
Keywords: Bivalve biomineralization; Crossed lamellar fabric; Tubules; Arda River; Lower Pleistocene